STUDI INTERAKSI OBAT-OBAT JANTUNG YANG DILAKUKAN TERHADAP ORANG SEHAT: TINJAUAN SISTEMATIS - Sumartin, Yunita; Sukandar, Elin Yulinah (Kartika : Jurnal Ilmiah Farmasi, 2024)
Patients with cardiovascular disease have a higher prevalence of drug interactions than other patient groups. Drug interactions may result from pharmacokinetic or pharmacodynamic mechanisms. This study is a systematic review that aims to identify drug interactions related to cardiac drugs. Article searches were conducted on PubMed and ScienceDirect databases to identify all articles on cardiac drug-drug interaction studies. The search started from articles published in 2013 to 2023. The keywords used in the article search were as follows: drug-drug interactions, cardiac patient, cardiac drug, cardiovascular drug, pharmacokinetics interaction, pharmacodynamic interaction combined with the boolean operator "AND". Study articles that met the requirements were entered into the study for review. The total number of articles identified from the database used was 805 articles; 7 duplicate articles were excluded; 84 articles were available in full text; but only 30 articles in accordance with the inclusion were reviewed. Potential drug interactions related to cardiac drugs were most common in the Angiotensin II Receptor Blocker (ARB) class of drugs. Other cardiac drug interactions occurred with angiotensin receptor-neprilysin inhibitors (ARNI), anticoagulants, antiplatelets, digoxin, calcium channel blockers and beta blockers. The effects of these cardiac drug interactions vary. To avoid the occurrence of drug interactions, co-administration of cardiac drugs should be administered with caution, dose adjustments may be required, and monitoring for possible adverse drug events should be done.